Differentiation in chemistry teaching - Kousa, Päivi (LUMAT-B: International Journal on Math, Science and Technology Education, 2016)
This article discusses how themes on science, technology, society and environment, connected to everyday life, besides interest and motivate towards learning, also can act as a good base for planning and carrying out of differentiating teaching. In the Unit of Chemistry Teacher Education in the University of Helsinki, the needs of Finnish teachers have been observed and research has been conducted to find out how it would be possible to support chemistry teacher-students and teachers already in the working life in the best possible way. With the help of suitable additional and further education, it is possible not only to answer to the need of support but also to offer versatile teaching materials and information, which come in handy in teaching all kinds of learners.